Marketing Substantiation of Measures on Innovative Development of the City of Izmail: Array - Yakovenko, Olena; Ivanenko, Iryna (Journal of Danubian Studies and Research, 2020)
The article analyzes the situation using the methods of SWOT-analysis, questionnaires using the CAWI method, and identifies problems in the functioning of the city of Izmail, Odessa region. Conducting correlation-regression analysis allowed identifying the factors that affect the level of tourist attractiveness of the city. On the basis of the analysis of literary sources, concrete measures are proposed for the city’s innovative development and enhancement of the tourist attractiveness.